NON-NATIVE AND NATIVE INVASIVE TERRESTRIAL PLANT SPECIES IN COMANA NATURAL PARK. CASE-STUDIES: AMORPHA FRUTICOSA AND CRATAEGUS MONOGYNA - MONICA DUMITRAŞCU; INES GRIGORESCU; GHEORGHE KUCSICSA; CARMEN-SOFIA DRAGOTĂ; MIHAELA NĂSTASE (Revue Roumaine de Géographie)
The paper is aiming to assess two of the major invasive terrestrial plant species (ITPS) which are affecting the ecological balance of the Comana Natural Park: Amorpha fruticosa (non-native) and Crataegus monogyna (native). The authors have undertaken their investigation in relation to the key environmental driving forcesresponsible for their introduction and spread: natural driving forces (relief, lithology and soil, climate, hydrology, vegetation, etc.) and human-induced driving forces (agricultural practices, grazing, forest exploitation, transport network). Taking into consideration the ecological importance of this natural protected area, the paper have as main purpose to make a complex assessment of these ITPS in terms of creating a GIS-based inventory of theirspreading areas in order draw up the distribution maps and identify the main particular environmental features of their habitats. Taking into consideration the intensification of the human-induced influences in various habitats, their geographical spread as well as their environmental driving forces, our approach aims at predicting the further distribution and extent of Amorpha and Crataegus in order put forward necessary management strategies for control. Based on this complex assessment, the potential users (foresters, environmentalists, etc.) will be able to predict the expanding of ITPS and identify their impact upon the natural habitat of some rarespecies, especially when talking about protected area’s conservative importance.